Elemental and Configural Associative Learning in Spatial Tasks: Could Zebrafish be Used to Advance Our Knowledge? - Buatois, Alexis; Gerlai, Robert (Frontiers in Behavioral Neuroscience, 2020)
Spatial learning and memory have been studied for several decades. Analyses of these processes pose fundamental scientific questions, but are also relevant from a biomedical perspective. The cellular, synaptic and molecular mechanisms underlying spatial learning have been intensively investigated, yet the behavioral mechanisms/strategies in a spatial task still pose unanswered questions. Spatial learning relies upon configural information about cues in the environment. However, each of these cues can also independently form part of an elemental association with the specific spatial position, and thus spatial tasks may be solved using elemental (single CS and US association) learning. Here, we first briefly review what we know about configural learning from studies with rodents. Subsequently, we discuss the pros and cons of employing a relatively novel laboratory organism, the zebrafish in such studies, providing some examples of methods with which both elemental and configural learning may be explored with this species. Last, we speculate about future research directions focusing on how zebrafish may advance our knowledge. We argue that zebrafish strikes a reasonable compromise between system complexity and practical simplicity, and that adding this species to the studies with laboratory rodents will allow us to gain better understanding of both the evolution of and the mechanisms underlying spatial learning. We conclude that zebrafish research will enhance translational relevance of our findings.